A review of the definitions of “effort” in articles published in Journal of the Experimental Behavior Analysis (JEAB) and Journal of Applied Behavior Analysis (JABA) (Research, Society and Development, 2024)
Through a literature review, this work mapped the behavioral analytical conceptions of “effort” presented in the first two journals specialized in behavior analysis: JEAB and JABA. The objective of this study was to identify, organize, and present different conceptualizations of the definition of effort in behavior analytic publications, as well as to categorize the experimental manipulations used to investigate this variable in studies published in JEAB and JABA. Articles that defined “effort” as one of the experimental variables were selected. Four categories of definitions of “effort” were found: (1) effort as requirements of the reinforcement schedule; (2) effort as a physical demand required for each response; (3) effort such as distance or height requirements; (4) effort as overall task complexity. A greater preponderance of Category 2 manipulations was observed in JEAB articles, and Category 3 in JABA. Despite the variety in definitions of effort, it is observed that (a) it is a concept that describes an intrinsic characteristic of the response if we consider that any action requires some level of effort and that (b) its definition varies according to the arrangement of contingencies in which the organism behaves.